10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Titanium alloy staples are widely used in gastrointestinal surgery. However, bacterial infection at the anastomotic site following surgery continues to be a significant concern due to the lack of effective treatment strategies. Inspired by shark skin structure, this study designed 5 sets of shark skin micro-textured staple surfaces with hydrophilic effects based on the Wenzel model. First, computational fluid dynamics (CFD) simulations were conducted to elucidate the regulatory influence of the surface on fluid velocity and wall shear stress in the gastrointestinal microenvironment. Wall shear stress is considered a key factor in reducing bacterial adhesion by physically obstructing the initial attachment of microorganisms. Subsequently, shark skin micro-textures were fabricated on the surface of the titanium sheet using laser processing technology. The wettability and morphological features of these micro-textured surfaces were systematically characterised via a contact angle metre and a scanning electron microscopy (SEM). Surface wettability, particularly hydrophilicity, is considered a key factor in enhancing fluid flow velocity in the gastrointestinal microenvironment, thereby increasing wall shear stress. Finally, a bacterial adhesion testing platform was established to evaluate the combined effects of these engineered surface properties (enhanced wall shear stress and wettability) on the anti-adhesion efficacy in inhibiting bacterial colonisation. The results showed that the prepared shark skin micro-textured surface of the titanium sheet could enhance fluid flow velocity and wall shear stress in the gastrointestinal microenvironment, thereby inhibiting bacterial adhesion and effectively preventing bacterial colonisation. This study provides a reference for the development of novel physically antimicrobial staple surfaces that actively regulate microfluidic flow fields.